SUCCESS STORY TO ERADICATE THE MARINE POLLUTION IN INTERNATIONAL STRAIT OR STRAIT FOR INTERNATIONAL TRADE - Hananto, Pulung Widhi Hari; Prananda, Rahandy Riski (Bagian Dasar-Dasar Ilmu Hukum & Hukum dan Masyarakat Fakultas Hukum Universitas Diponegoro, 2020)
Marine pollution has a significant impact on the waters of the coastal states, especially in the strait routes used for international trade. The traffic density of large ships which is not proportional to the wide geographical conditions, makes the Strait of Malacca a potential area that is prone to high marine pollution. This article aims to examine the use of the Marine Electronic Highway in the Malacca Strait and the success story which is applied to the territorial waters of other countries that have the same conditions. The results of the study show that in the Dover strait region, the French and British Governments are collaborating by investing in infrastructure to regulate the navigation of these areas. Meanwhile, at The Torres Straits, the Australian Government implemented a Pilotage policy by requiring ships passing through to pay a maintenance fee of 3% for the conservation of the waterways and security zones. However, the Indonesian and Malaysian governments had to negotiate beforehand to determine the delimitation of their respective maritime boundaries in Malacca Straits.